2018
DOI: 10.1016/j.neuroimage.2016.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Visual field biases for near and far stimuli in disparity selective columns in human visual cortex

Abstract: When visual objects are located in the lower visual field, human observers perceive objects to be nearer than their real physical location. Conversely, objects in the upper visual field are viewed farther than their physical location. This bias may be linked to the statistics of natural scenes, and perhaps the ecological relevance of objects in the upper and lower visual fields (Previc, 1990; Yang & Purves, 2003). However, the neural mechanisms underlying such perceptual distortions have remained unknown. To t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 59 publications
7
37
1
Order By: Relevance
“…3). While the potential correlation between disparity tuning and retinotopic elevation has not been directly assessed in cats or monkeys, a recent study compiling data from several publications in macaque V1 (Sprague et al 2015), and a recent fMRI study in humans (Nasr and Tootell 2018) found the same relationship that we report here for the mouse. Not surprisingly, the natural distribution of binocular disparities…”
Section: Discussionsupporting
confidence: 80%
“…3). While the potential correlation between disparity tuning and retinotopic elevation has not been directly assessed in cats or monkeys, a recent study compiling data from several publications in macaque V1 (Sprague et al 2015), and a recent fMRI study in humans (Nasr and Tootell 2018) found the same relationship that we report here for the mouse. Not surprisingly, the natural distribution of binocular disparities…”
Section: Discussionsupporting
confidence: 80%
“…These thin-and thick-type columns were localized based on their stereoselectivity and color selectivity, respectively. Their columnar (radial) organization was shown based on (1) similarity between the activity patterns evoked across cortical layers and (2) comparison of the level of correlation across versus within layers (Nasr et al, 2016;Nasr and Tootell, 2018). The existence of these columns and their differential sensitivity to additional functional properties are consistent with findings based on invasive techniques in nonhuman primates (NHPs; for review, see Tootell and Nasr, 2017).…”
Section: Introductionsupporting
confidence: 53%
“…Our experiments specifically tested whether the asymmetry in global visual processing is reflected as a differential sensitivity to low-SF stimuli evoked within near-versus far-preferring clusters, distributed within stereoselective columns. Although NHP (Adams and Zeki, 2001;Tanabe et al, 2005;Chen et al, 2008) and human (Nasr and Tootell, 2018) studies reported that near-compared with far-preferring neurons are more frequently found in the cortical representation of the LVF compared with the UVF, to our knowledge, no previous study has compared the sensitivity of near-versus far-preferring neural clusters, in any visual area, at low SFs.…”
Section: Introductionmentioning
confidence: 89%
“…Perceptually, human observers are better at detecting targets defined by crossed (near) disparity (Breitmeyer, Julesz, & Kropfl, 1975) and overestimate the distance of objects in the upper visual field (Ooi, Wu, & He, 2001;Wallach & O'Leary, 1982;Yang & Purves, 2003), while they are better at detecting targets defined by uncrossed (far) disparity and underestimate the distance of objects in the lower visual field (Breitmeyer, Battaglia, & Bridge, 1977). This bias has also been observed physiologically: clustered regions that respond to near and far stimuli are preferentially located in retinotopic regions representing the upper and lower visual fields of V2/3, respectively (Nasr & Tootell, 2018). Although all stimuli in the tilt condition had equal absolute global disparity, the anisotropic representation of near and far disparity in the upper and lower visual field likely resulted in a larger response to the 0 tilt stimuli, thus biasing the distribution of voxel tilt preferences.…”
Section: Discussionmentioning
confidence: 90%